2014
DOI: 10.1093/molbev/msu194
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Sites Implicate Functional Convergence of the Hearing Gene Prestin among Echolocating Mammals

Abstract: Echolocation is a sensory system whereby certain mammals navigate and forage using sound waves, usually in environments where visibility is limited. Curiously, echolocation has evolved independently in bats and whales, which occupy entirely different environments. Based on this phenotypic convergence, recent studies identified several echolocation-related genes with parallel sites at the protein sequence level among different echolocating mammals, and among these, prestin seems the most promising. Although pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 40 publications
2
77
0
2
Order By: Relevance
“…This suggests that the observation of a derived substitution in a background species does not necessarily preclude a functional effect on the protein, and that pure patterns of convergence rarely exists when taxonomic sampling depth increases [38]. Furthermore, in various examples of such as prestin, RNAse1, rhodopsin, Na+/K+-ATPase, functional convergence is observed along with the presence of multiple sites displaying parallel substitutions [14,[39][40][41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the observation of a derived substitution in a background species does not necessarily preclude a functional effect on the protein, and that pure patterns of convergence rarely exists when taxonomic sampling depth increases [38]. Furthermore, in various examples of such as prestin, RNAse1, rhodopsin, Na+/K+-ATPase, functional convergence is observed along with the presence of multiple sites displaying parallel substitutions [14,[39][40][41].…”
Section: Resultsmentioning
confidence: 99%
“…In order to detect genomic changes involved in the convergent hearing properties of these echolocating lineages, several studies have searched and identified parallel amino acid substitutions in candidate genes with a known hearing-related function such as Dfnb59, Otof, and prestin [9][10][11][12]. Subsequently, in vitro assays demonstrated that parallel substitutions in prestin, a protein known to be critical for high-frequency hearing [13], account for the functional convergence in key parameters of prestin [14]. This shows that searching for molecular parallelism in candidate genes provided insights into the convergent adaptations to high frequency hearing; however, the mechanisms underlying the convergent vocalization aspect of echolocation remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Note that Prestin (a.k.a. SLC26A5), known to be involved in echolocation (Li, Liu, Shi, & Zhang, 2010;Liu, Qi, Zhou, Ren, & Shi, 2014;Liu et al, 2010), is the most significant convergent gene out of the 6,332 ones of the dataset. Still for studying echolocation, Shen, Liang, Li, Murphy, and Zhang (2012) screened three genes, namely CDH23, PCDH15 and OTOF, pointing out that "Convergent evolution and expression patterns of OTOF suggest the potential role of nerve and brain in echolocation".…”
Section: Application: Convergent Genes Related To Echolocationmentioning
confidence: 99%
“…These studies have highlighted genes that have been repeatedly targeted during the evolution of a given trait. For example, the evolution of echolocation in bats and toothed whales appears to be driven, in part, by common mutations in the genes Prestin [12, 13] and Cdh23 [14, 15]; cardiac glycoside toxin resistance in numerous disparate vertebrates and invertebrates can be explained by identical amino acid substitutions in the enzyme Na+/K+-ATPase [16]; and the repeated convergent evolution of the sodium ion transporter NaV1.7 in hibernating mammals and mole-rats is believed to impart insensitivity to the accumulation of CO2 [17]. These studies, and many others, demonstrate that common selective pressures can drive common mutations in relevant genes.…”
Section: Introductionmentioning
confidence: 99%